FORMULASI STRATEGI BISNIS BERSAING PADA FAKULTAS EKONOMI UNIVERSITAS YARSI - , Muhammad Norman Prayudi Putra; , Ely Susanto, SIP, MBA, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Education industry today still has a high enough appeal to be developed, as proven by the increase in higher education institutions in Jakarta annually. Besides competition from existing universities, there are both public and private demands to better develop FE YARSI. Competition in education occurs because one or more of the factors that exist as well as looking at the pressure of the competition between educational institutions or an opportunity to improve their position. Competition has resulted in a change in consumer behavior in choosing a college that universities must do to analyze and evaluate existing strategies in order to continue to grow and thrive. In doing the internal and external assessment strategy formulation, it is necessary to maximize the implementation of the strategy, using internal and external analysis of the economics faculty, they can use the strength and reduce weakness to face the threats and maximize the opportunities they have. Errors in the implementation of strategies can impact the decline in the number of students.